Effect of co-medication on the pharmacokinetic parameters of phenobarbital in asphyxiated newborns - Šíma, M; Pokorná, P; Hronová, K; Slanař, O (Physiological research, 2015)
Phenobarbital is an anticonvulsive drug widely used in newborns with hypoxic-ischemic encephalopathy. The objective of our study was to describe possible effect of frequently co-administered medications (dopamine, dobutamine, norepinephrine, furosemide, phenytoin, and analgesics) on the phenobarbital pharmacokinetics in full term newborns with hypoxic-ischemic encephalopathy. Phenobarbital pharmacokinetic parameters (standardized intravenous loading dose was 10-20 mg/kg, maintenance dose 2-6 mg/kg/day) were computed using non-compartmental analysis. Co-medication was evaluated throughout the whole treatment period up to 5 days. Volume of distribution, clearance, and half-life median values (95 % CI) for phenobarbital in the whole study population (n=37) were 0.48 (0.41-0.56) l/kg, 0.0034 (0.0028-0.0040) l/h/kg, and 93.7 (88.1-99.2) h, respectively. Phenobarbital pharmacokinetic parameters were not significantly affected by vasoactive drugs (dopamine, dobutamine, and norepinephrine), furosemide, phenytoin, or analgesics. Furthermore, no dose-dependent alteration of phenobarbital pharmacokinetic parameters was noted for vasoactive medication at doses equivalent to cumulative vasoactive-inotropic score (area under the curve in a plot of vasoactive-inotropic score against time) 143.2-8473.6, furosemide at cumulative doses of 0.2-42.9 mg/kg, or phenytoin at cumulative doses of 10.3-46.2 mg/kg. Phenobarbital pharmacokinetics was not affected by investigated co-administered drugs used in newborns with hypoxic-ischemic encephalopathy in real clinical settings.
Keywords: výsledek terapie; Male; Hypoxia-Ischemia, Brain; analgetika; lékové interakce; fenobarbital; kombinovaná farmakoterapie; Prospective Studies; mužské pohlaví; Drug Therapy, Combination; mozková hypoxie a ischemie; Anticonvulsants; Treatment Outcome; novorozenec; Phenobarbital; lidé; ženské pohlaví; Humans; Drug Interactions; Infant, Newborn; antikonvulziva; Analgesics; vazokonstriktory; Vasoconstrictor Agents; Female; prospektivní studie